Screening for Chronic Kidney Disease in Family Members of Dialysis Patients. - Jais Kumar ,Ghiasuddin Butt ,Faran Maqbool (Journal of Rawalpindi Medical College, 2017)
To study the prevalence of chronic kidney disease in family members of dialysis patients Methods: In this cross-sectional observational study relatives of incident dialysis patient were enrolled. Family members of patients of all ages with history of diabetes mellitus, hypertension, family history of chronic kidney disease, chronic pyelonephritis and autoimmune diseases were included. Relatives already on renal replacement therapy, Hepatitis B and C, HIV reactive patients and with chronic heart and liver failure, chronic infections and septicemia patients were excluded . Results: Out of these 200 participants, majority (72%) were male. Minimum age of the study population was 18 years and maximum age was 66 years. Mean age was 35.5 ± 9.93 years. Frequency of risk factors in study population showed that out of 200 participants 15% had hypertension, 6% had diabetes, 2.5% had renal stone disease and 74% participants did not have any risk factor. Blood pressure was normal in 83% participants. Blood glucose was normal in 92.5%. Conclusion: Screening of the family members of ESRD patients is important for the prevention of kidney disease in other family members.